2016
DOI: 10.20341/gb.2016.009
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the shale oil and gas potential of Westphalian mudstone successions in the Campine Basin, NE Belgium (well KB174): Palaeoenvironmental and palaeogeographical controls

Abstract: ABSTRACT. Westphalian mudstones in the Hechtel-Hoef well, Campine Basin, Belgium, were examined for their hydrocarbon potential by means of Rock-Eval pyrolysis. These mudstones have an average TOC content of 3.6% and mean S2 and Hydrogen Index values of respectively 7.9 and 164.2 mg/g and contain a mixture of kerogen types II and III. This indicates that in contrast to the Westphalian coal seams, these successions are not predominantly gas-prone but could also generate higher molecular-weight hydrocarbons and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Gas storage in unconventional shale reservoirs is a complex multiparameter problem. Studies to date identify organic matter characteristics (total organic carbon (TOC) content, thermal maturation, and kerogen type), mineralogy, pore system, moisture, pressure, and temperature as important parameters in assessment of gas sorption capacity of shales. Organic matter in shales has been considered as the first contributor to gas sorption capacity of shales. Previous studies have reported the positive correlation between TOC content and methane sorption on black shales of North America and Europe. , Thermal maturity of organic matter has a positive effect on the methane sorption capacity of shales, and this is ascribed to the increase in the organic micropores and/or change in chemistry characteristics of organic matter during thermal maturation. , When it comes to the type of organic matter of shales, sorption capacity on TOC basis was reported to increase in order: type I < type II < type III, and this was attributed to the larger micropore surface area of humic kerogen compared to other maceral composition when the organic matter is highly mature and the increasing kerogen aromaticity of organic matter in the progression from type I to type III kerogen. In addition to organic matter, pores of inorganic constituents (clay minerals) accommodate additional sorbed gas due to their developed internal surface area, and contribute appreciable amounts of gas sorption in clay-rich shales under dry condition. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Gas storage in unconventional shale reservoirs is a complex multiparameter problem. Studies to date identify organic matter characteristics (total organic carbon (TOC) content, thermal maturation, and kerogen type), mineralogy, pore system, moisture, pressure, and temperature as important parameters in assessment of gas sorption capacity of shales. Organic matter in shales has been considered as the first contributor to gas sorption capacity of shales. Previous studies have reported the positive correlation between TOC content and methane sorption on black shales of North America and Europe. , Thermal maturity of organic matter has a positive effect on the methane sorption capacity of shales, and this is ascribed to the increase in the organic micropores and/or change in chemistry characteristics of organic matter during thermal maturation. , When it comes to the type of organic matter of shales, sorption capacity on TOC basis was reported to increase in order: type I < type II < type III, and this was attributed to the larger micropore surface area of humic kerogen compared to other maceral composition when the organic matter is highly mature and the increasing kerogen aromaticity of organic matter in the progression from type I to type III kerogen. In addition to organic matter, pores of inorganic constituents (clay minerals) accommodate additional sorbed gas due to their developed internal surface area, and contribute appreciable amounts of gas sorption in clay-rich shales under dry condition. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Concerns about the accurate evaluation of gas content and diffusion kinetics have led to many experimental studies about gas sorption on shales. Significant progress has been achieved in the controls on sorption capacity of shales. However, data on high-temperature high-pressure sorption isotherms of shales are still scare. In particular, the burial depth of the Paleozoic shales in the Upper Yangtze region of China is mostly in a range of 2000–4000 m, which indicates that the temperature and pressure of shale reservoirs are in the range of 60–120 °C and 20–40 MPa, assuming the hydrostatic pressure and normal geothermal gradients (0.01 MPa/m, 0.03 °C/m).…”
Section: Introductionmentioning
confidence: 99%
“…This led to a net export of dissolution products such as silica, that was redistributed to other surrounding sandstones, such as the coarser grained bleached sandstones that acted as a sink, since this mesogenetic AQ cement type is more common in these sandstones. As stated above, based on mass balance calculations, Muchez et al (1992) calculated that the released amount of fluids with dissolved organic acids was more than enough for explaining the observed iron-reduction, even without taking the intercalated organic Westphalian shales into account (see also Vandewijngaerde et al, 2016). Part or all of the released ferric iron was incorporated into the mesogenetic zoned ankerite and siderite, indicating that the system with regard to Fe acted as a (partly) closed system.…”
Section: Open Versus Closed System Diagenesismentioning
confidence: 96%